CRISPR-Cas9 Gene Editing for Targeting Cancer Stem Cells in Glioblastoma Multiforme - Mahar, Saifullah Khan; Amara; Ali, Ammara; Javid , Amina; Khan , Bilal (Indus Journal of Bioscience Research, 2025)
This research investigates the possibility of CRISPR-Cas9 gene editing in targeting glioblastoma multiforme (GBM) cancer stem cells (CSCs) for increasing CSC sensitivity to conventional treatments and suppressing tumor growth. A quantitative method was used, with a sample of 36 GBM patients diagnosed and treated at major tertiary care centers in Pakistan, namely Aga Khan University Hospital (Karachi), Shaukat Khanum Memorial Cancer Hospital (Lahore), and Pakistan Institute of Medical Sciences (Islamabad). Tumor tissue samples were obtained at the time of surgical resection and processed to harvest CSCs based on certain markers like CD133 and Nestin using fluorescence-activated cell sorting (FACS). The CRISPR-Cas9 gene editing was subsequently conducted on isolated CSCs to knock out genes of interest involved in stemness and therapy resistance, such as SOX2, MGMT, and Wnt/β-catenin. The efficacy of CRISPR-Cas9 gene editing was evaluated by pre- and post-CRISPR tumor growth rates, proliferation assays in vitro, and neurosphere formation. Multiple regression analysis showed that CRISPR-Cas9 gene editing greatly enhanced therapy sensitivity (B = 1.427, p = 0.000), with pre-CRISPR tumor growth rate (B = -0.512, p = 0.009) and initial tumor size (B = -0.312, p = 0.040) having a negative correlation with the efficacy of treatment. Moreover, increased MGMT expression (B = -0.312, p = 0.050) was related to decreased therapy sensitivity. ANOVA test showed significant variability among the efficacies of different delivery methods for CRISPR-Cas9, including viral vectors, nanoparticles, and electroporation (F = 4.56, p = 0.008), and pointed towards optimizing the delivery strategies to achieve efficient gene editing. CRISPR-Cas9 shows promise for GBM treatment, but delivery issues and off-target effects need resolution to enable future clinical applications.